Investigation of Hyaluronan Synthase 2 and CD44 immune reactivity as a biomarker to predict Progesterone-Resistant Endometrial Hyperplasia without atypia: A retrospective case-control study - Emine Boybay; Remzi Atilgan; Şehmus Pala; Tuncay Kuloğlu; Gökhan Artaş (Indian Journal of Pathology and Microbiology)
Background/Aims: In our study, the effect of hyaluronan synthase 2 (HAS2) and CD44 immunoreactivity as a predictive biomarker in the prediction of progesterone-resistant endometrial hyperplasia (EH) cases without atypia was investigated. Settings and Design: In this retrospective study, HAS2 and CD44 immunoreactivity in the endometrial tissues of 60 patients diagnosed with EH and treated with progesterone and 20 patients diagnosed with proliferative endometrium (PE) were evaluated. Materials and Methods: Eighty patients were divided into four groups. Group 1 (G1) (n = 20) = PE group, G2 (n = 20) = EH group without atypia, G3 (n = 20) = group with continued EH with treatment, G4 (n = 20) = EH with treatment without atypia. Statistical Analysis: Intergroup evaluation was done with One-way ANOVA and posthoc tukey test. P < 0.05 values were considered statistically significant. Results: The HAS2 immunoreactivity score of G2 and G3 was higher than G1 and G4. On the other hand, there was no difference between G1 and G4. When G2 and G3 were compared, HAS2 immunoreactivity scores were significantly increased in G3. When CD44 immunoreactivity was compared with G1, a significant increase was detected in G2, G3, and G4. However, CD44 immunoreactivity scores were similar in G2, G3, and G4. Conclusion: HAS2 immunoreactivity may be an immunohistochemical biomarker in predicting EH cases without atypia resistant to progesterone therapy. Since CD44 immunoreactivity is increased in all EH groups without atypia, it is not effective in predicting treatment resistance.